123k views
4 votes
Solve for the indicated variable. Include all of your work in your answer. Submit your solution.

C=5(f-32) over 9 so C=5(f-32) / 9

Can someone please explain this step by step. I don't understand this at all...

User Gildas
by
5.4k points

2 Answers

4 votes

Assuming you have to solve it for f, you have to rewrite the equation in a form like f = ...

So in the form it is now, you're solving for C. You're not actually going to get values for f or C, for that you'd need more information.

So how do we convert the C = ... form into an f = ... form? Step by step you want to isolate f using simple rules:

step 1) I want to get rid of the 5 so we're dividing left and right by 5:

C/5 = 5(f-32)/(9*5) this simplifies to C/5 = (f-32)/9

step 2) Get rid of the 9 by multiplying by 9 left and right:

9*C/5 = 9*(f-32)/9 simplifies to f-32

step 3) I want to get rid of the -32 so I'm adding 32 left and right:

9*C/5 + 32 = f-32 + 32 simplifies to 9*C/5 + 32 = f

Now just swap left and right, and we get:

f = 9C/5 + 32

All you have to learn is the basic tricks like adding left and right, multiplying left and right. Hope this helps.



User Dmitrydwhite
by
5.3k points
4 votes

Remark

I will assume you are looking for F.


C = (5(F - 32))/(9) Multiply both sides by 9


9*C = (5(F - 32))/(9) * 9 divide by 5 on both sides


(9*C)/(5)= (5(F - 32))/(5) \\ \\ (9C)/(5) = F - 32

Add 32 to both sides.

9*C/5 + 32 = F


User Avinash A
by
5.6k points